Negative electrode material, negative electrode and lithium ion battery

By introducing MXene-based three-dimensional composite materials, nanosilicon particles and carbon coatings into the silicon anode material of lithium-ion batteries, the problem of volume expansion of lithium-silicon alloys is solved, and higher cycle life and rate performance are achieved.

CN119786582APending Publication Date: 2025-04-08BYD CO LTD

Patent Information

Application Number
CN202510028048.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The silicon negative electrode material in lithium-ion batteries expands in volume due to the formation of lithium-silicon alloy, causing the cracking and powdering of the active material, affecting the cycle life of the battery.

Method used

The negative electrode material composed of MXene-based three-dimensional composite material, nanosilicon particles and carbon clad layer are uniformly distributed in amorphous state on the surface, between layers and pores of MXene-based three-dimensional composite material, forming a three-dimensional conductive network structure, alleviating volume expansion and improving cyclic stability.

Benefits of technology

By reducing volume expansion and improving conductivity, the cycle life of lithium-ion batteries is significantly extended, and the rate performance and lithium-ion transmission performance of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786582A_ABST
    Figure CN119786582A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode material, a negative electrode and a lithium ion battery. The negative electrode material comprises an MXene-based three-dimensional composite material, nano silicon particles and a carbon coating layer, wherein the MXene-based three-dimensional composite material comprises a CNTs layer and an MXene material with a multi-layer structure, and the CNTs layer is arranged between two adjacent layers of the MXene material; the nano silicon particles are positioned in the MXene-based three-dimensional composite material; and the carbon coating layer covers the surfaces of the nano silicon particles and the surface and interlayer of the MXene-based three-dimensional composite material. The negative electrode material disclosed by the invention can avoid volume expansion of the silicon particles and prolong the cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of negative electrode materials, and in particular, to a negative electrode material, a negative electrode and a lithium ion battery. Background Art

[0002] Unlike traditional graphite anodes based on deintercalation reactions, silicon anodes can undergo reversible alloying reactions with lithium, achieving a lithium storage capacity far higher than that of graphite anodes, and are expected to become the anode material for the next generation of lithium-ion batteries. However, silicon itself has poor conductivity and poor kinetic performance; at the same time, during the lithium intercalation process, the silicon anode will undergo a large volume expansion (about 300%) due to the formation of lithium-silicon alloys, causing the active material to rupture and pulverize, and continuously undergo violent side reactions with the electrolyte, resulting in the continuous growth of the solid electrolyte interface (SEI), while causing the internal conductive network of the electrode to be destroyed, affecting the overall cycle life of the battery. Summary of the invention

[0003] The purpose of the present disclosure is to provide a negative electrode material, a negative electrode and a lithium ion battery, which can avoid the volume expansion of silicon particles and improve the cycle life of the battery.

[0004] In order to achieve the above-mentioned objectives, the first aspect of the present disclosure provides a negative electrode material, comprising a MXene-based three-dimensional composite material, nano-silicon particles and a carbon coating layer; wherein the MXene-based three-dimensional composite material comprises a carbon nanomaterial and a plurality of stacked MXene sheets, and at least part of the carbon nanomaterial is located between two adjacent MXene sheets; the nano-silicon particles are located between the MXene sheets of the MXene-based three-dimensional composite material and / or on the surface and / or in the pores of the MXene sheets; and the carbon coating layer is coated on the surface of the MXene-based three-dimensional composite material.

[0005] Optionally, the chemical formula of the MXene sheet is as shown in the following formula (1): M n+1 X n Formula (1); In formula (1), M is selected from one or more transition metals, including Ti, Zr, Nb, Cr, Mo and V; X includes C and / or N; 0<n≤3.

[0006] Optionally, the number of MXene sheets contained in the particles of the MXene-based three-dimensional composite material is 2-5; the interlayer distance between any two adjacent MXene sheets is 1.22-2 nm; The carbon nanomaterial includes carbon nanotubes and carbon nanofibers; the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; the carbon nanotubes have a diameter of 1-10 nm and an aspect ratio of more than 500; the carbon nanofibers have a diameter of 5-10 nm and a length of 1-15 μm.

[0007] Optionally, based on the total weight of the negative electrode material, the content of the MXene-based three-dimensional composite material is 48-69.9% by weight, the content of the nano-silicon particles is 30-50% by weight, and the content of the carbon coating layer is 0.1-2% by weight.

[0008] Optionally, based on the total weight of the MXene-based three-dimensional composite material, the content of the carbon nanomaterial is 5-20% by weight, and the total content of the MXene sheet is 80-95% by weight.

[0009] Optionally, the negative electrode material has a D50 particle size of 4-10 μm and a BET specific surface area of ​​1.0-6.0 m 2 / g; the thickness of the carbon coating layer is 5-20nm.

[0010] A second aspect of the present disclosure provides a method for preparing a negative electrode material, comprising the following steps: S1, mixing the carbon nanomaterial, the surfactant, the MXene material and the solvent, performing solid-liquid separation and drying to obtain a MXene-based three-dimensional composite material; S2, contacting the MXene-based three-dimensional composite material with a first mixed gas including silane gas and a first inert carrier gas, performing a vapor deposition process, and obtaining a silicon deposition product; S3, contacting the silicon deposition product with a second mixed gas including a carbon coating gas and a second inert carrier gas to perform a carbon coating treatment.

[0011] Optionally, in step S1, the weight ratio of the carbon nanomaterial: surfactant: MXene material is 0.053-0.25: 0.001-0.005: 1; Based on the total weight of the mixture obtained by the mixing process, the content of the solvent is 10-95% by weight.

[0012] Optionally, in step S1, the MXene material comprises stacked MXene sheets; the number of sheets in the MXene material is 2-5; the interlayer distance between any two adjacent MXene sheets is 1.22-2 nm; the BET specific surface area of ​​the MXene material is 100-1000 m 2 / g; The carbon nanomaterial includes carbon nanotubes and carbon nanofibers; the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; the carbon nanotubes have a diameter of 1-10 nm and an aspect ratio of more than 500; the carbon nanofibers have a diameter of 5-10 nm and a length of 1-15 μm; The surfactant is selected from one or more of quaternary ammonium salt compounds and alkylamine compounds; wherein the quaternary ammonium salt compounds include polydiallyldimethylammonium chloride and hexadecyltrimethylammonium bromide; and the alkylamine compounds are selected from hexadecylamine and octadecylamine.

[0013] Optionally, in step S1, the mixing treatment conditions include: under an inert atmosphere, a mixing temperature of -10 to 10°C, and a mixing time of 0.5-10h; the inert atmosphere is selected from one or more of argon, nitrogen and helium; The drying conditions include: drying temperature of 45-150° C. and drying time of 0.5-10 h.

[0014] Optionally, in step S2, the conditions of the vapor deposition process include: The vapor deposition temperature is 400-900° C., the vapor deposition time is 0.5-5 h, and the vapor deposition pressure is 0.1-5 MPa; in the first mixed gas, the volume flow rate of the silane gas is 10-200 sccm, and the volume flow rate of the first inert carrier gas is 50-400 sccm; The silane gas includes SiH4; the first inert carrier gas is selected from one or more of argon, nitrogen and helium; Preferably, step S2 comprises: repeating the vapor deposition process 2-8 times.

[0015] Optionally, in step S3, the conditions of the carbon coating treatment include: The treatment temperature is 500-800°C, the treatment time is 0.5-5h, and the treatment pressure is 0.1-2MPa; the volume flow rate of the carbon coating gas is 10-50sccm, and the volume flow rate of the second inert carrier gas is 40-100sccm; The carbon coating gas is selected from one or more hydrocarbon gases with a carbon atom number of 1-4; preferably, the carbon coating gas is selected from one or more methane, ethylene, acetylene and ethane; the second inert carrier gas is selected from one or more argon, nitrogen and helium.

[0016] A third aspect of the present disclosure provides a negative electrode material prepared according to the method described in the second aspect of the present disclosure.

[0017] A fourth aspect of the present disclosure provides a negative electrode, comprising the negative electrode material described in the first aspect or the third aspect of the present disclosure.

[0018] A fifth aspect of the present disclosure provides a lithium-ion battery, comprising the negative electrode described in the fourth aspect of the present disclosure.

[0019] Through the above technical scheme, the present disclosure provides a negative electrode material, a negative electrode and a lithium ion battery, wherein the nano silicon particles in the negative electrode material are uniformly distributed on the surface, interlayer and pores of the MXene-based three-dimensional composite material in an amorphous state, which can alleviate the crystallization agglomeration of silicon during the battery cycle and improve the cycle stability of the material; the silicon particles have a nanometer size, which can also shorten the diffusion path of lithium ions and alleviate the volume expansion. The MXene-based three-dimensional composite material includes a carbon nanomaterial filled in the interlayer, which can form a 3D conductive network structure in the composite matrix, improve the conductivity of the material, and alleviate the volume expansion of the internal silicon particles; at the same time, the carbon nanomaterial can support the layer structure of the MXene material, avoid the structural collapse and stacking of the MXene material, and thus improve the specific surface area, lithium ion transmission performance and rate performance of the obtained negative electrode material. The interlamellar gap of the MXene-based three-dimensional composite material can contribute to the transportation and diffusion of lithium ions, which can greatly improve the rate performance of the silicon negative electrode; the surface of the MXene-based three-dimensional composite material in the negative electrode material is coated with a carbon coating layer, which can isolate the nano silicon in the negative electrode material from direct contact with the outside world and reduce the occurrence of interface side reactions.

[0020] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings: Figure 1 XRD patterns of negative electrode materials obtained in Example 1 and Comparative Example 1 of the present disclosure; Figure 2 The pressure-conductivity relationship curve of the negative electrode materials obtained in Example 1 and Comparative Example 1 of the present disclosure is shown. DETAILED DESCRIPTION

[0022] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0023] A first aspect of the present disclosure provides a negative electrode material, comprising a MXene-based three-dimensional composite material, nano-silicon particles and a carbon coating layer; wherein the MXene-based three-dimensional composite material comprises a carbon nanomaterial and a plurality of stacked MXene sheets, and at least a portion of the carbon nanomaterial is located between two adjacent MXene sheets; the nano-silicon particles are located between the MXene sheets of the MXene-based three-dimensional composite material and / or on the surface and / or in the pores of the MXene sheets; and the carbon coating layer is coated on the surface of the MXene-based three-dimensional composite material.

[0024] The present disclosure provides a negative electrode material, wherein the nano silicon particles in the negative electrode material are uniformly distributed on the surface, between layers and in the pores of the MXene-based three-dimensional composite material in an amorphous state, which can alleviate the crystallization agglomeration of silicon during the battery cycle and improve the cycle stability of the material; the silicon particles have a nanometer size, which can also shorten the diffusion path of lithium ions and alleviate the volume expansion. The MXene-based three-dimensional composite material includes a carbon nanomaterial filled between layers, which can form a 3D conductive network structure in the composite matrix, improve the conductivity of the material, and alleviate the volume expansion of the internal silicon particles; at the same time, the carbon nanomaterial can support the layer structure of the MXene material, avoid the structural collapse and stacking of the MXene material, and thus improve the specific surface area, lithium ion transmission performance and rate performance of the obtained negative electrode material. The interlamellar gap of the MXene-based three-dimensional composite material can help the transportation and diffusion of lithium ions, and can greatly improve the rate performance of the silicon negative electrode; the surface of the MXene-based three-dimensional composite material in the negative electrode material is coated with a carbon coating layer, which can isolate the nano silicon in the negative electrode material from direct contact with the outside world and reduce the occurrence of interface side reactions.

[0025] In a specific embodiment, the chemical formula of the MXene sheet is shown in the following formula (1): M n+1 X n Formula (1); In formula (1), M is selected from one or more transition metals, including Ti, Zr, Nb, Cr, Mo and V; X includes C and / or N; 0<n≤3. The MXene material with the chemical composition shown in formula (1) has a high specific surface area, high mechanical strength and good electrical conductivity, and is an ideal base material for constructing a nanocomposite structure, which can further improve the performance of the negative electrode material.

[0026] In a specific embodiment, the chemical formula of the MXene sheet includes one or more of Ti3C2, Ti4C3, Ti2C and Nb2C.

[0027] The MXene material used in the present disclosure can be purchased through common commercial channels or prepared by known methods.

[0028] In one embodiment, the number of MXene flakes contained in the particles of the MXene-based three-dimensional composite material is 2-5, preferably 2-4; the interlayer spacing between any two adjacent MXene flakes is 1.22-2nm, preferably 1.5-2nm; the use of a MXene material having the structure provided in this embodiment (especially having the nanosheet spacing in this embodiment) can improve the specific surface area, lithium ion transport performance and rate performance of the resulting negative electrode material, and can also avoid the collapse of the MXene flake structure.

[0029] In one embodiment, the carbon nanomaterial includes carbon nanotubes and carbon nanofibers; the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; the carbon nanotubes have a diameter of 1-10 nm, preferably 2-5 nm, and an aspect ratio of 500 or more, preferably 600-800; the carbon nanofibers have a diameter of 5-10 nm, preferably 6-8 nm, and a length of 1-15 μm, preferably 2-5 μm. Using carbon nanotubes and / or carbon nanofibers having the structure in this embodiment, a CNTs conductive layer can be more effectively constructed between the layers of the MXene material to improve the performance of the negative electrode material. The carbon nanotubes and carbon nanofibers in the present disclosure can be purchased through ordinary commercial channels, or prepared by known methods.

[0030] In one embodiment, based on the total weight of the negative electrode material, the content of the MXene-based three-dimensional composite material is 48-69.9% by weight, the content of the nano-silicon particles is 30-50% by weight, and the content of the carbon coating layer is 0.1-2% by weight; Preferably, based on the total weight of the negative electrode material, the content of the MXene-based three-dimensional composite material is 54-64.8% by weight, the content of the nano-silicon particles is 35-45% by weight, and the content of the carbon coating layer is 0.2-0.8% by weight. When the content of each component in the negative electrode material is within the range provided in this embodiment, especially within the preferred range, the cycle capacity retention rate of the negative electrode material in the battery can be further improved.

[0031] In the present disclosure, the negative electrode material may also include a surfactant introduced in the preparation process; however, the content of the surfactant is extremely low and can be ignored.

[0032] In one embodiment, based on the total weight of the MXene-based three-dimensional composite material, the content of the carbon nanomaterial is 5-20% by weight, and the total content of the MXene sheet is 80-95% by weight; preferably, the content of the carbon nanomaterial is 5-10% by weight, and the total content of the MXene sheet is 90-95% by weight. When the content of the components of the MXene-based three-dimensional composite material is within the range of this embodiment, especially within the preferred range, it is more conducive to improving the performance of the negative electrode material.

[0033] In one embodiment, the D50 particle size of the negative electrode material is 4-10 μm, preferably 5-8 μm; the BET specific surface area is 1.0-6.0 m 2 / g, preferably 1.5-4m 2 / g, the thickness of the carbon coating layer is 5-20nm, preferably 10-15nm, and further preferably 13-15nm; the conductivity of the negative electrode material (under 100Mpa) is 0.09-0.13mS / cm, preferably 0.10-0.13mS / cm; the negative electrode material provided by the present disclosure has higher electronic conductivity and ion conductivity, is more conducive to lithium ion transmission, and improves the rate performance of the battery.

[0034] A second aspect of the present disclosure provides a method for preparing a negative electrode material, comprising the following steps: S1, mixing the carbon nanomaterial, the surfactant, the MXene material and the solvent, performing solid-liquid separation and drying to obtain a MXene-based three-dimensional composite material; S2, contacting the MXene-based three-dimensional composite material with a first mixed gas including silane gas and a first inert carrier gas, performing a vapor deposition process, and obtaining a silicon deposition product; S3, contacting the silicon deposition product with a second mixed gas including a carbon coating gas and a second inert carrier gas to perform a carbon coating treatment.

[0035] The present disclosure provides a method for preparing a negative electrode material. First, a carbon nanomaterial, a surfactant and a MXene material are mixed and dried. The carbon nanomaterial can be made to form a carbon nanomaterial conductive layer located between MXene material layers by an electrostatic self-assembly method to form a three-dimensional conductive network structure to obtain a MXene-based three-dimensional composite material, wherein the surfactant can improve the uniformity of the carbon nanomaterial and can also improve the interaction between the carbon nanomaterial and the MXene material, so that the carbon nanomaterial can more easily enter the interlayer of the MXene material and improve the filling effect of the carbon nanomaterial between the sheets; then the obtained MXene-based three-dimensional composite material and silane gas are subjected to vapor deposition treatment to deposit nanosilicon in the interlayers and gaps of the three-dimensional composite material, improve the deposition uniformity of nanosilicon, and improve the cycle stability of the negative electrode material during the battery cycle; the collapse and stacking of the two-dimensional structure of the MXene material caused by the nanosilicon deposition can also be avoided, which is beneficial to increase the specific surface area of ​​the negative electrode material, improve lithium ion transmission and battery rate; then the silicon deposition product is subjected to carbon coating treatment, the coated individuals are cracked, and amorphous carbon is deposited on the surface of the silicon deposition product.

[0036] In a specific embodiment, the method for preparing a negative electrode material provided by the present disclosure comprises the following steps: (1) mixing a carbon nanomaterial, a surfactant and a first solvent to obtain a first solution; and mixing MXene with a second solvent to obtain a second solution; (2) The first solution and the second solution are mixed, solid-liquid separated and vacuum dried to obtain a MXene-based three-dimensional composite material; in the present disclosure, the carbon nanomaterial is evenly distributed between the layers of the MXene material. The carbon nanomaterial acts as an interlayer spacer, which is beneficial to stabilize the layer structure of the MXene and avoid collapse. At the same time, it acts as a bridge to connect the MXene layers to form a three-dimensional conductive network; (3) then contacting the MXene-based three-dimensional composite material with a first mixed gas including silane gas and a first inert carrier gas, and performing a vapor deposition process to obtain a silicon deposition product; in the present disclosure, in the product after the vapor deposition, nano-silicon is distributed between layers or in pores of the MXene-based three-dimensional composite material; (4) The silicon deposition product is contacted with a second mixed gas including a carbon coating gas and a second inert carrier gas to perform a carbon coating treatment, and the surface of the obtained MXene-based three-dimensional composite material of the negative electrode material has an amorphous carbon coating.

[0037] In one embodiment, in step S1, the weight ratio of the carbon nanomaterial: surfactant: MXene material is 0.053-0.25: 0.001-0.005: 1; preferably 0.1-0.15: 0.002-0.004: 1; Based on the total weight of the mixture obtained by the mixing process, the content of the solvent is 10-95% by weight, preferably 80-90% by weight. According to the raw material ratio in this embodiment, especially according to the preferred raw material ratio, a MXene-based three-dimensional composite material with better performance can be prepared, which is beneficial to improving the cycle stability of the negative electrode material.

[0038] In a specific embodiment, the MXene material comprises stacked MXene sheets; the number of sheets in the MXene material is 2-5, preferably 3-5; the interlayer distance between any two adjacent MXene sheets is 1.22-2nm, preferably 1.3-1.8nm; the BET specific surface area of ​​the MXene material is 100-1000m 2 / g, preferably 150-300m 2 / g; The carbon nanomaterial includes carbon nanotubes and carbon nanofibers; the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; the carbon nanotubes have a diameter of 1-10 nm, preferably 2-5 nm, and an aspect ratio of 500 or more, preferably 600-1000; the carbon nanofibers have a diameter of 5-10 nm, preferably 6-8 nm, and a length of 1-15 μm, preferably 3-8 μm.

[0039] In a specific embodiment, in step S1, the surfactant is selected from one or more of quaternary ammonium salt compounds and alkylamine compounds; Wherein, the quaternary ammonium salt compound includes polydiallyldimethylammonium chloride and hexadecyltrimethylammonium bromide; the alkylamine compound is selected from hexadecylamine and octadecylamine. The use of the surfactant type in this embodiment can make the carbon nanomaterial have a better filling effect between the layers of the MXene material. The surfactant used in the present disclosure can be purchased through ordinary commercial channels or prepared by known methods.

[0040] In one embodiment, in step S1, the mixing treatment conditions include: under an inert atmosphere, the mixing temperature is -10 to 10°C, the mixing time is 0.5-10h, preferably, the mixing temperature is -5 to 5°C, and the mixing time is 1-3h; the inert atmosphere is selected from one or more of argon, nitrogen and helium; The solid-liquid separation process can be carried out by conventional operations such as filtration; The conditions for the solid drying treatment include: a drying temperature of 45-150° C. and a drying time of 0.5-10 h; preferably, a drying temperature of 80-120° C. and a drying time of 3-6 h. By treating according to the conditions in this embodiment, a composite matrix with better performance can be prepared.

[0041] In one embodiment, in step S2, the conditions of the vapor deposition treatment include: the vapor deposition temperature is 400-900°C, the vapor deposition time is 0.5-5h, and the vapor deposition pressure is 0.1-5MPa; in the first mixed gas, the volume flow rate of the silane gas is 10-200sccm, and the volume flow rate of the first inert carrier gas is 50-400sccm; the silane gas includes SiH4; the first inert carrier gas is selected from one or more of argon, nitrogen and helium; Preferably, the conditions of the vapor deposition treatment include: a vapor deposition temperature of 500-750°C, a vapor deposition time of 1-3h, and a vapor deposition pressure of 0.2-2MPa; in the first mixed gas, the volume flow rate of the silane gas is 50-150sccm, and the volume flow rate of the first inert carrier gas is 100-300sccm; performing vapor deposition treatment according to the process conditions in this embodiment, especially according to the preferred vapor deposition treatment, can further improve the deposition uniformity of nano-silicon, and can also control and improve the accuracy of silicon deposition amount.

[0042] In a preferred embodiment, step S2 includes repeating the vapor deposition process 2-5 times to further improve the deposition uniformity and the accuracy of the deposition amount of the silicon particles.

[0043] In the present disclosure, the vapor deposition process is carried out in a fluidized bed, and the nano-silicon deposition can be made more uniform through the fluidization reaction.

[0044] In one embodiment, in step S3, the carbon coating treatment conditions include: a treatment temperature of 500-800°C, a treatment time of 0.5-5h, a treatment pressure of 0.1-2MPa; a volume flow rate of the carbon coating gas of 10-50sccm, and a volume flow rate of the second inert carrier gas of 40-100sccm; Preferably, the carbon coating treatment conditions include: treatment temperature of 550-650°C, treatment time of 1.0-2.0h, treatment pressure of 0.2-1MPa; volume flow rate of carbon coating gas of 20-40sccm, volume flow rate of the second inert carrier gas of 60-90sccm; The carbon coating gas is selected from one or more hydrocarbon gases with carbon atoms of 1-4; preferably, the carbon coating gas is selected from one or more methane, ethylene, acetylene and ethane; the second inert carrier gas is selected from one or more argon, nitrogen and helium. According to the process conditions in this embodiment, especially according to the preferred process conditions, a better carbon coating effect can be obtained, and the coating uniformity of the carbon layer is higher. In the present disclosure, the carbon coating treatment is carried out in a fluidized bed, and the fluidized reaction can increase the gas-solid contact area, increase the reaction rate, and improve the production efficiency.

[0045] A third aspect of the present disclosure provides a negative electrode material prepared according to the method described in the second aspect of the present disclosure.

[0046] A fourth aspect of the present disclosure provides a negative electrode, comprising the negative electrode material described in the first aspect or the third aspect of the present disclosure.

[0047] The negative electrode provided by the present disclosure includes a copper foil current collector and a negative electrode coating, wherein the negative electrode coating includes the negative electrode material, a negative electrode conductive agent and a negative electrode binder; optionally, based on the total weight of the negative electrode coating, the content of the negative electrode material is 80-97% by weight, the content of the negative electrode conductive agent is 1-10% by weight and the balance is the negative electrode binder; preferably, based on the total weight of the negative electrode coating, the content of the negative electrode material is 85-93% by weight, the content of the negative electrode conductive agent is 1.5-2.5% by weight and the balance is the negative electrode binder. When the negative electrode coating has the composition provided in this embodiment, the lithium ion battery can have better performance.

[0048] In a specific embodiment, the thickness of the negative electrode coating is 20-100 μm, preferably 30-50 μm.

[0049] In the present disclosure, the negative electrode conductive agent and the negative electrode binder can be materials conventionally selected in the art, for example, the negative electrode conductive agent can be selected from one or more of Super P conductive agent, multi-walled carbon nanotubes, single-walled carbon nanotubes and carbon black; the negative electrode binder can be selected from one or more of polyacrylic acid, carboxymethyl cellulose, polyurethane, polyvinylidene fluoride and polyimide. The negative electrode coating can be obtained by conventional slurry coating, and the coating can be performed by conventional operations.

[0050] A fifth aspect of the present disclosure provides a lithium-ion battery, comprising the negative electrode described in the fourth aspect of the present disclosure.

[0051] In a specific embodiment, the lithium-ion battery also includes a positive electrode, an electrolyte and a separator, etc., which can be of the types conventionally selected in the art. For example, the positive electrode can be a lithium sheet, etc.; the electrolyte can include a lithium salt, an electrolyte solvent and an electrolyte additive, wherein the lithium salt can be lithium fluorophosphate, the electrolyte solvent can be ethylene carbonate and diethyl carbonate, etc.; the electrolyte additive can be fluoroethylene carbonate; the separator can be made of materials such as Celgard 2400 polypropylene film and polyethylene.

[0052] In the present disclosure, the lithium-ion battery is assembled using conventional methods in the art.

[0053] The present disclosure is further described in detail by way of examples. The raw materials used in the examples can all be obtained through commercial sources.

[0054] The XRD test of the negative electrode piece was performed using a Bruker D8 Advance. The test conditions included: (1) the negative electrode piece was cut into a shape that met the XRD test requirements and then placed in a test mold; (2) the negative electrode piece was subjected to an XRD test with a detection range of 2θ of 5-90° and a scanning speed of 5° / min; The interlayer spacing of MXene sheets contained in the particles of the MXene-based three-dimensional composite material in the negative electrode material is calculated by the Bragg equation, including: d=nλ / 2sinθ (d represents the interlayer spacing, nm; n represents the diffraction number; λ represents the diffraction wavelength; θ represents the diffraction half-angle of the peak position, in degrees).

[0055] The interlayer spacing and carbon tube size are detected by SEM or TEM. The SEM test method includes: cutting the pole piece by CP (ion cutting), performing scanning electron microscope test (SEM), observing the cross-sectional morphology, and determining the interlayer spacing and the tube diameter of CNTs by distance measurement. The TEM test method includes: dispersing the electrode into anhydrous ethanol by ultrasonic, taking one to three drops of the dispersion and dropping them onto a copper mesh, and performing a TEM test after drying: by observing the thickness of the particle surface layer, the thickness of the carbon coating layer, the diameter and length of the CNTs, and the interlayer spacing of the MXene material can be obtained. The interlayer spacing of the MXene material in this disclosure is based on XRD, supplemented by SEM and TEM.

[0056] The D50 particle size of the sample was measured using a laser particle size analyzer.

[0057] The specific surface area of ​​the samples was obtained using BET test.

[0058] In the following examples and comparative examples, the MXene material used was obtained through commercial channels, and the chemical formula was Ti3C2. The number of layers of MXene nanosheets in the MXene material was 3, and the distance between two adjacent MXene nanosheets was 1.3 nm; the BET specific surface area was 300 m 2 / g; CNTs are single-walled carbon nanotubes; the diameter of CNTs is 2nm and the aspect ratio is 600; The conductivity of the negative electrode material was measured using PRCD3100 (IEST Yiyuan Energy Technology). The specific steps included: weighing 1g of silicon-carbon powder and placing it in the test mold of the instrument, using the four-probe mode, applying a pressure range of 10-200MPa, and holding the pressure for 10s to obtain a curve of the change in powder conductivity with pressure.

[0059] Nanosilicon in the negative electrode material can be obtained by titration with NaOH aqueous solution; the content of the carbon coating layer is obtained by TG testing; the content of MXene in the MXene-based three-dimensional composite material is determined by ICP measurement of the metal element content.

[0060] Example 1 (1) Concentrated sulfuric acid and concentrated nitric acid (weight ratio of 3:1) are used to condense and reflux CNTs (carbon nanomaterials), and the CNTs powder cooled to room temperature after reflux is dispersed in distilled water for multiple washing, and distilled water is added to prepare a solution, and then a surfactant PDDA (polydimethyl ammonium chloride) is added to form a first solution; (2) Mixing MXene with distilled water to form a second solution; adding the first solution to the second solution, stirring and mixing at low temperature under the protection of an inert gas (nitrogen) (i.e., mixing treatment), the mixing temperature is 0 ° C, and the mixing time is 2 h; The weight ratio of CNTs (carbon nanomaterials): surfactant: MXene material is 0.1:0.003:1; based on the total weight of the mixture obtained by the mixing process, the content of the solvent is 90% by weight; (3) The solution is vacuum filtered (solid-liquid separation treatment), and the obtained material is vacuum dried (drying temperature is 120°C, drying time is 4 hours), and after drying, a MXene-CNTs composite material (MXene-based three-dimensional composite material) can be obtained; (4) placing the MXene-based three-dimensional composite material into a fluidized bed and maintaining the temperature at 500 °C; (5) introducing a mixed gas of 60 sccm of silane and 100 sccm of argon (first inert carrier gas) into the fluidized bed for reaction at 500°C for 2 h; (6) Pass 100 sccm of argon gas for 30 minutes; (7) Repeat steps (5) to (6) 5 times; (8) The temperature of the fluidized bed was adjusted to 600°C, and a mixed gas of 40 sccm of acetylene (carbon coating gas) and 80 sccm of argon (second inert carrier gas) was introduced for carbon coating treatment for 1 hour; the temperature was cooled to room temperature to obtain a composite silicon negative electrode material.

[0061] The XRD spectrum of the negative electrode material obtained in this example is as follows Figure 1 As shown by Figure 1 It can be seen that compared with the peak position of the standard MXene material (7.21°), the peak position of the negative electrode material obtained in this embodiment is significantly shifted to the left, indicating that the embedding of CNTs increases the interlayer spacing of the MXene material.

[0062] The curves of the conductivity of the negative electrode materials obtained in this embodiment and comparative example 1 as a function of pressure are shown in FIG. Figure 2 As shown by Figure 2 It can be seen that the conductivity of the negative electrode material obtained in Example 1 increases more obviously with increasing pressure, indicating that the addition of CNTs has a significant effect on improving the conductivity.

[0063] Example 2 This embodiment refers to the method in Embodiment 1, and the difference from Embodiment 1 is that: In the step of preparing the MXene-based three-dimensional composite material, the raw material ratio was adjusted so that the weight ratio of CNTs: surfactant: MXene material was 0.08:0.001:1; the rest of the process was the same as in Example 1 to prepare the negative electrode material.

[0064] Example 3 This embodiment refers to the method in Embodiment 1, and the difference from Embodiment 1 is that: In the step of preparing the MXene-based three-dimensional composite material, the raw material ratio was adjusted so that the weight ratio of CNTs: surfactant: MXene material was 0.3:0.006:1; the rest of the process was the same as in Example 1 to prepare the negative electrode material.

[0065] Example 4 This embodiment refers to the method in Embodiment 1, and the difference from Embodiment 1 is that: In the step of obtaining nano-silicon by vapor deposition, the process conditions are adjusted as follows: A mixed gas of 40 sccm of silane and 80 sccm of argon (the first inert carrier gas) was introduced into the fluidized bed; the rest of the process was the same as in Example 1, and the negative electrode material was prepared.

[0066] Example 5 This embodiment refers to the method in Embodiment 1, and the difference from Embodiment 1 is that: In the step of obtaining nano-silicon by vapor deposition, the process conditions are adjusted as follows: A mixed gas of 250 sccm of silane and 500 sccm of argon (the first inert carrier gas) was introduced into the fluidized bed; the rest of the process was the same as in Example 1, and the negative electrode material was prepared.

[0067] Example 6 This embodiment refers to the method in Embodiment 1, and the difference from Embodiment 1 is that: In the carbon coating treatment, the process conditions were adjusted as follows: a mixed gas of 50 sccm of acetylene (carbon coating gas) and 100 sccm of argon (second inert carrier gas) was introduced; the rest of the process was the same as in Example 1, and the negative electrode material was prepared.

[0068] Example 7 This embodiment refers to the method in Embodiment 1, and the difference from Embodiment 1 is that: In the carbon coating treatment, the process conditions are adjusted as follows: A mixed gas of 80 sccm of acetylene (carbon coating gas) and 160 sccm of argon (second inert carrier gas) was introduced; the rest of the process was the same as in Example 1, and the negative electrode material was prepared.

[0069] Comparative Example 1 This comparative example refers to the method in Example 1, and the difference from Example 1 is that: MXene material is directly used for vapor deposition treatment, and the step of adding CNTs composite matrix in steps (1)-(3) is not performed; the rest of the process is the same as in Example 1, and a composite silicon negative electrode material is prepared.

[0070] The XRD spectrum of the negative electrode material obtained in this comparative example is as follows Figure 1 As shown by Figure 1 It can be seen that compared with the peak position of the standard MXene material (7.21°), the interlayer spacing between MXene materials has not changed.

[0071] Comparative Example 2 This comparative example refers to the method in Example 1, and the difference from Example 1 is that: No carbon coating treatment was performed, and the remaining process was the same as in Example 1 to prepare a negative electrode material.

[0072] Comparative Example 3 This comparative example refers to the method in Example 1, and the difference from Example 1 is that the step of vapor deposition of nano-silicon is replaced by mechanical mixing, including: mechanically mixing the MXene-based three-dimensional composite material with nano-silicon particles (particle size of 10 nm), and the conditions of mechanical mixing include two steps of wet grinding and spray drying; wherein in the wet grinding: the weight ratio of the MXene-based three-dimensional composite material to the nano-silicon particles in the solvent (ethanol) is 1:0.5:0.5, the rotation speed is 200 rpm, the time is 6 hours, and the ball-to-material ratio is 4; in the spray drying: the feed temperature of the slurry obtained by wet grinding is 25°C, and the outlet temperature is 120°C; the pressure is 0.3 MPa; the carrier gas is nitrogen or argon; the remaining processes are the same as in Example 1, and the negative electrode material is prepared.

[0073] Comparative Example 4 This comparative example refers to the method in Example 1, and the difference from Example 1 is that in the step of preparing the MXene-based three-dimensional composite material, no surfactant is added, and the rest of the process is the same as in Example 1 to prepare the negative electrode material.

[0074] The structural properties and component contents of the negative electrode materials obtained in the above examples and comparative examples, the conductivity of the negative electrode materials and other data are listed in the following Tables 1 and 2.

[0075] Table 1

[0076] Table 2

[0077] Test Case This test example is used to illustrate the application effect of the negative electrode materials prepared in the above embodiments and comparative examples in lithium-ion batteries.

[0078] Using water as a solvent, the negative electrode material obtained in the embodiment or comparative example, the Super P conductive agent (negative electrode conductive agent) and the polyacrylic acid binder (negative electrode binder) are mixed uniformly in a mass ratio of 8:1:1 to obtain a slurry, which is then applied to a copper foil current collector and placed in a vacuum oven at 100° C. for 24 hours to obtain a negative electrode, the negative electrode comprising a negative electrode coating, the content of the negative electrode material in the negative electrode coating being 80% by weight, the content of the negative electrode conductive agent being 10% by weight, and the content of the negative electrode binder being 10% by weight.

[0079] The lithium sheet was used as the negative electrode, Celgard 2400 polypropylene film was used as the battery separator, the electrolyte was a mixed solution of 1 mol / L lithium hexafluorophosphate (LiPF6) in ethylene carbonate (EC) and diethyl carbonate (DEC) (solvent volume ratio of 1:1) as the electrolyte, and 5.0 wt% of fluoroethylene carbonate was added as the electrolyte additive.

[0080] The positive and negative electrode materials, separator, electrolyte and additives are assembled into a CR2032 button battery using conventional methods in the art.

[0081] The electrochemical properties of silicon-carbon negative electrode materials were tested using a Blue Electric test system (model CT2011A). The assembled button cell was discharged at a constant current of 100 mA / g to 0.005 V at room temperature, and then charged at a constant current of 100 mA / g to 1.5 V. The discharge specific capacity and charge specific capacity of the first cycle were recorded, and the coulombic efficiency (%) of the battery was calculated = charge specific capacity / discharge specific capacity × 100%. This process was used for cycling, and the capacity retention rate after 100 cycles was calculated.

[0082] Rate performance test: The assembled button cell was discharged at a constant current of 100mA / g to 0.005V at room temperature, and then charged to 1.5V at constant currents of 100mA / g and 5A / g respectively. The charging capacity at different currents was recorded, and the capacity retention rate was calculated: 5A / g capacity retention rate of constant current charging (%) = (charging capacity at 5A / g / charging capacity at 100mA / g) × 100%.

[0083] The test results of using the negative electrode materials obtained in the examples and comparative examples in lithium-ion batteries are listed in the following Table 3.

[0084] Table 3

[0085] According to the data in Tables 1 to 3 above, it can be seen that: Comparative Example 1 does not introduce carbon nanomaterials. Comparing Examples 1-7 with Comparative Example 1, the negative electrode materials prepared according to the method of the present disclosure in Examples 1-7 have higher first coulombic efficiency, 100 cycle capacity retention rate and capacity retention rate at a current density of 5A / g, and have better cycle performance; the embedding of CNTs in the negative electrode material prepared in Example 1 greatly improves the charge and discharge capacity of the material at a high rate, and the rate performance advantage is obvious; Comparative Example 2 does not carry out carbon coating. Comparing Examples 1-7 with Comparative Example 2, the negative electrode materials prepared according to the method disclosed in Examples 1-7 have higher first coulombic efficiency, 100 cycle capacity retention rate and capacity retention rate at a current density of 5 A / g, and have better cycle performance; In Comparative Example 3, nano-silicon particles were not deposited by vapor deposition process, but nano-silicon was introduced by mechanical mixing. Comparing Examples 1-7 with Comparative Example 3, the negative electrode materials prepared by the method of the present disclosure in Examples 1-7 had higher first coulombic efficiency, 100 cycle capacity retention rate and capacity retention rate at a current density of 5 A / g, and had better cycle performance; In Comparative Example 4, no surfactant was added, and the spacing of the MXene nanosheets in the obtained negative electrode material was 1.3 nm, which was smaller than the spacing of the MXene nanosheets in the negative electrode materials in Examples 1-7, indicating that the addition of surfactants in Examples 1-7 is more conducive to CNTs entering the interlayers of MXene nanosheets to increase the interlayer spacing; and the negative electrode materials prepared according to the method of the present disclosure in Examples 1-7 have higher first coulombic efficiency, 100 cycle capacity retention rate and capacity retention rate at a current density of 5 A / g, and have better cycle performance; Comparing Example 2 with Example 3, in Example 2, the preparation reaction was carried out according to the optimized weight ratio of CNTs: surfactant: MXene material provided in the present disclosure, the content of nano-silicon in the negative electrode material obtained in Example 2 was within the preferred range of the present disclosure, and the content of MXene material and the content of CNTs in the MXene-based three-dimensional composite material were within the optimized range of the present disclosure, and the negative electrode material of Example 2 had higher first coulombic efficiency, 100 cycle capacity retention rate and capacity retention rate at a current density of 5 A / g, and had better cycle performance; Further comparing Example 2 with Example 1, the weight ratio of CNTs: surfactant: MXene material in Example 1 is within the further preferred range provided by the present disclosure, and the negative electrode material of Example 1 has higher first coulombic efficiency, 100 cycle capacity retention rate and capacity retention rate at a current density of 5 A / g, and has better cycle performance; Comparing Example 4 with Example 5, the step of vapor deposition of nano-silicon in Example 4 is carried out according to the optimized process conditions provided in the present disclosure, and the component content of the negative electrode material obtained in Example 4 is within the preferred range provided in the present disclosure; and the negative electrode material of Example 4 has higher first coulombic efficiency, 100 cycle capacity retention rate and capacity retention rate at a current density of 5A / g, and has better cycle performance; Further comparing Example 4 with Example 1, the process conditions of vapor deposition of nano-silicon in Example 1 are within the further preferred range of the present disclosure, and the negative electrode material obtained in Example 1 has a higher 100-cycle capacity retention rate and a capacity retention rate at a current density of 5A / g, and has better cycle performance; and the negative electrode material obtained in Example 1 has a higher first coulombic efficiency and has better battery performance; Comparing Example 6 with Example 7, Example 6 adopts the optimized process conditions provided by the present disclosure for carbon coating treatment, and the carbon coating thickness of the negative electrode material prepared in Example 6 is within the optimized range. The negative electrode material obtained in Example 6 has higher first coulombic efficiency, 100 cycle capacity retention rate and capacity retention rate at a current density of 5A / g, and better cycle performance; Further comparing Example 6 with Example 1, the conditions of the carbon coating treatment in Example 1 are within a further preferred range, the negative electrode material obtained in Example 1 has a more suitable carbon coating layer thickness, and the negative electrode material of Example 1 has a higher first coulombic efficiency, 100 cycle capacity retention rate and capacity retention rate at a current density of 5 A / g, and has better cycle performance.

[0086] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0087] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0088] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A negative electrode material, characterized in that: It includes a MXene-based three-dimensional composite material, nano-silicon particles and a carbon coating layer; wherein the MXene-based three-dimensional composite material includes a carbon nanomaterial and a plurality of stacked MXene sheets, and at least part of the carbon nanomaterial is located between two adjacent MXene sheets; the nano-silicon particles are located between the MXene sheets of the MXene-based three-dimensional composite material and / or on the surface and / or in the pores of the MXene sheets; and the carbon coating layer is coated on the surface of the MXene-based three-dimensional composite material.

2. The negative electrode material according to claim 1, characterized in that The chemical formula of the MXene sheet is shown in the following formula (1): M n+1 X n Formula (1); In formula (1), M is selected from one or more transition metals, including Ti, Zr, Nb, Cr, Mo and V; X includes C and / or N; 0<n≤3.

3. The negative electrode material according to claim 1, characterized in that The number of MXene sheets contained in the particles of the MXene-based three-dimensional composite material is 2-5; the interlayer distance between any two adjacent MXene sheets is 1.22-2 nm; The carbon nanomaterial includes carbon nanotubes and carbon nanofibers; the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; the carbon nanotubes have a diameter of 1-10 nm and an aspect ratio of more than 500; the carbon nanofibers have a diameter of 5-10 nm and a length of 1-15 μm.

4. The negative electrode material according to claim 1, characterized in that Based on the total weight of the negative electrode material, the content of the MXene-based three-dimensional composite material is 48-69.9% by weight, the content of the nano-silicon particles is 30-50% by weight, and the content of the carbon coating layer is 0.1-2% by weight.

5. The negative electrode material according to claim 1, characterized in that Based on the total weight of the MXene-based three-dimensional composite material, the content of the carbon nanomaterial is 5-20% by weight, and the total content of the MXene sheet is 80-95% by weight.

6. The negative electrode material according to claim 1, characterized in that The D50 particle size of the negative electrode material is 4-10 μm, and the BET specific surface area is 1.0-6.0 m 2 / g; the thickness of the carbon coating layer is 5-20nm.

7. A method for preparing a negative electrode material, characterized in that: The following steps are involved: S1, mixing the carbon nanomaterial, the surfactant, the MXene material and the solvent, performing solid-liquid separation and drying to obtain a MXene-based three-dimensional composite material; S2, contacting the MXene-based three-dimensional composite material with a first mixed gas including silane gas and a first inert carrier gas, performing a vapor deposition process, and obtaining a silicon deposition product; S3, contacting the silicon deposition product with a second mixed gas including a carbon coating gas and a second inert carrier gas to perform a carbon coating treatment.

8. The method according to claim 7, characterized in that In step S1, the weight ratio of the carbon nanomaterial: surfactant: MXene material is 0.053-0.25: 0.001-0.005: 1; Based on the total weight of the mixture obtained by the mixing process, the content of the solvent is 10-95% by weight.

9. The method according to claim 7, characterized in that: In step S1, the MXene material comprises stacked MXene sheets; the number of sheets in the MXene material is 2-5; the interlayer distance between any two adjacent MXene sheets is 1.22-2 nm; the BET specific surface area of ​​the MXene material is 100-1000 m 2 / g; The carbon nanomaterial includes carbon nanotubes and carbon nanofibers; the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; the carbon nanotubes have a diameter of 1-10 nm and an aspect ratio of more than 500; the carbon nanofibers have a diameter of 5-10 nm and a length of 1-15 μm; The surfactant is selected from one or more of quaternary ammonium salt compounds and alkylamine compounds; wherein the quaternary ammonium salt compounds include polydiallyldimethylammonium chloride and hexadecyltrimethylammonium bromide; and the alkylamine compounds are selected from hexadecylamine and octadecylamine.

10. The method according to claim 7, characterized in that In step S1, the mixing treatment conditions include: under an inert atmosphere, a mixing temperature of -10 to 10°C, and a mixing time of 0.5 to 10 hours; the inert atmosphere is selected from one or more of argon, nitrogen and helium; The drying conditions include: drying temperature of 45-150° C. and drying time of 0.5-10 h.

11. The method according to claim 7, characterized in that In step S2, the conditions of the vapor deposition process include: The vapor deposition temperature is 400-900° C., the vapor deposition time is 0.5-5 h, and the vapor deposition pressure is 0.1-5 MPa; in the first mixed gas, the volume flow rate of the silane gas is 10-200 sccm, and the volume flow rate of the first inert carrier gas is 50-400 sccm; The silane gas includes SiH4; the first inert carrier gas is selected from one or more of argon, nitrogen and helium; Preferably, step S2 comprises: repeating the vapor deposition process 2-8 times.

12. The method according to claim 7, characterized in that In step S3, the carbon coating treatment conditions include: The treatment temperature is 500-800°C, the treatment time is 0.5-5h, and the treatment pressure is 0.1-2MPa; the volume flow rate of the carbon coating gas is 10-50sccm, and the volume flow rate of the second inert carrier gas is 40-100sccm; The carbon coating gas is selected from one or more hydrocarbon gases with a carbon atom number of 1-4; preferably, the carbon coating gas is selected from one or more methane, ethylene, acetylene and ethane; the second inert carrier gas is selected from one or more argon, nitrogen and helium.

13. A negative electrode material prepared according to the method according to any one of claims 7 to 12.

14. A negative electrode, characterized in that: The negative electrode material comprises any one of claims 1 to 6 and 13.

15. A lithium ion battery, characterized in that: Comprising the negative electrode as claimed in claim 14.

Citation Information

Patent Citations

  • Composite material, preparation method and application thereof, electrode and lithium ion battery

    CN110752364A

  • Negative electrode active material, and preparation method and application thereof

    CN112038601A

  • Metal-nitrogen battery positive electrode catalyst material and preparation method thereof

    CN118610493A

  • High-dispersity carbon nanotube slurry and preparation method thereof

    CN119108145A

  • Preparation method of modified MXene material and immunosensor

    CN119118130A

Cited By

  • Negative plate as well as preparation method and application thereof

    CN122291409A